Biocatalytic synthesis and ordered self-assembly of silica nanoparticles via a silica-binding peptide - Gungormus, Mustafa (Beilstein Journal of Nanotechnology, 2023)
Achieving scalable and economic methods for manufacturing ordered structures of nanoparticles is an ongoing challenge. Ordered structures of SiO2 nanoparticles have gained increased attention due to the great potential they offer in filtering, separation, drug delivery, optics, electronics, and catalysis. Biomolecules, such as peptides and proteins, have been demonstrated to be useful in the synthesis and self-assembly of inorganic nanostructures. Herein, we describe a simple Stöber-based method wherein both the synthesis and the self-assembly of SiO2 nanoparticles can be facilitated by a silica-binding peptide (SiBP). We demonstrate that the SiBP acts as a multirole agent when used alone or in combination with a strong base catalyst (NH3). When used alone, SiBP catalyzes the hydrolysis of precursor molecules in a dose-dependent manner and produces 17–20 nm SiO2 particles organized in colloidal gels. When used in combination with NH3, the SiBP produces smaller and more uniformly distributed submicrometer particles. The SiBP also improves the long-range self-assembly of the as-grown particles into an opal-like structure by changing the surface charge, without any need for further modification or processing of the particles. The results presented here provide a biomimetic route to the single-step synthesis and assembly of SiO2 nanoparticles into colloidal gels or opal-like structures.
Keywords: biocatalysis; biomimetics; nanoparticle; peptide; self-assembly; silica